Psychometric validation of the PTSD Checklist-5 among female Filipino migrant workers. Issue 1 (1st January 2019) - Hall, Brian J.; Yip, Paul S. Y.; Garabiles, Melissa R.; Lao, Chao Kei; Chan, Edward W. W.; Marx, Brian P.
ABSTRACT: Migrant populations are at increased risk for exposure to traumatic life events. Presently, there are no reliable and valid screening instruments for posttraumatic stress disorder (PTSD) among Filipino migrant workers, a population that numbers over 2.3 million worldwide. This study evaluated the psychometric properties of the PTSD Checklist for DSM-5 (PCL-5) in a sample of female Filipino migrant workers in Macao (SAR), China, in two studies. The first examined the reliability (internal and test-retest), convergent validity (with depression, anxiety, and rumination), and discriminant validity (with pain and social support) in a sample of 131 participants. The second study established criterion validity of the PCL-5 using the PTSD module of the Mini-International Neuropsychiatric Interview (MINI), delivered by a female Filipino psychologist as the criterion, in a sample of 100 participants. Results indicated excellent internal consistency (Cronbach's alpha = 0.95) and moderate 10-day test-retest reliability (ρ = 0.58, p < .001). PCL-5 scores correlated strongly with scores on measures of depression (ρ = 0.71, p < .001), anxiety (ρ = 0.61, p < .001), and rumination (ρ = 0.68, p < .001), supporting convergent validity. Discriminant validity was demonstrated by a weaker association with scores on measures of pain (ρ = 0.33, p < .001) and social support (ρ = −0.11, p = .22). The diagnostic accuracy of the scale was good (AUC = 0.87). The optimal cutoff score of 25 optimized sensitivity (0.89) while maintaining adequate specificity (0.73), with a weighted Kappa of κ[1]) = 0.82. Our results demonstrated that the PCL-5 is a reliable and valid screening instrument for use among female Filipino migrant workers.